Communication of a person with a literary text as an "honoured interlocutor" - Elena V. Ryaguzov (Saratov State University, 2022)
The article presents the results of the scientifi c refl ection on the communication of a person with a literary text. The latter is understood widely as a product of any aesthetic creative activity of the author. It acts as the author's open invitation to a dialogue. The author uses the anthropological metaphor and philosopheme "honored interlocutor" proposed by a. A. Ukhtomsky as a key concept in the refl ection on the interaction of a person with cultural artifacts. Communication of an individual with a literary text is positioned as co-existence, i.e. it is a way of being together in a single mode of "We", an existential dialogue between the addresser, the addressee and the polyphonic Others who are represented in the world of art by various fi gures, heroes, characters and texts. The article analyses the network of intersecting interactions between all the subjects of aesthetic communication. Attention is focused on personal characteristics (incorporated cultural capital, specifi cs of motivation, goal-setting, peculiarities of values and interests), and on possible emotional and behavioural statuses and subject positions of the addressee (observer, interlocutor, co-creator). The researcher argues that by entering into communication with literary texts, the viewer / reader / listener understands, accepts and internalises only those of them that he deserves due to his subjective activity, aesthetic competence, responsible actions and personal eff orts. However, he receives as a gift those rewards that he himself deserves, finding them in the transformed inner world and in the opening spiritual perspectives.